A prospective evaluation of magnetic resonance cholangiopancreatography in patients with suspected bile duct obstruction. Issue 5 (1st November 1998) - Adamek, H E; Albert, J; Weitz, M; Breer, H; Schilling, D; Riemann, J F
Abstract : Background —The value of magnetic resonance cholangiopancreatography (MRCP) is under debate. Aims —To assess the diagnostic accuracy of MRCP and endoscopic retrograde cholangiopancreatography (ERCP) and to determine whether MRCP may help to prevent unnecessary interventional procedures. Methods —Eighty six patients with suspected common bile duct obstruction who presented between January and December 1996 were enrolled. Twenty six were excluded due to anatomical reasons or because MRCP or ERCP could not be performed successfully. Results of MRCP were interpreted by two radiologists and a gastroenterologist unaware of clinical diagnosis. Final diagnosis was determined by ERCP and histopathological findings or a follow up of at least 12 months. Results —MRCP images of diagnostic quality were obtained in all 60 patients. Thirteen patients had a clear bile duct. Sensitivity and specificity for the detection of any abnormality (n=47) were 89% and 92%, and for the detection of malignancy (n=27) 81% and 100%, respectively. These results were equivalent to the respective figures of ERCP (91% and 92% for any abnormality, and 93% and 94% for malignant diseases). Conclusions —MRCP is as sensitive as ERCP in the evaluation of bilary tract diseases. As the specificity of this non-invasive technique is close to 100%, MRCP may prevent inappropriate invasive explorations of the common bile duct and pancreatic duct.